PENGEMBANGAN PERMAINAN MOTORIK MOTION FOOT KELAS I SDN 01 KALIWUNGU - Laksmi Dewi, Norma; Galuh Danawati, Murtyas; Frendy , Frendy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Reading can be interpreted as language skills. Reading is a receptive ability in children. A child's world is a world of play, children who learn are children who play, and children who do play activities are children who also learn. This research aims to evaluate the effectiveness of using motion foot media in improving reading difficulties in class I at SDN 01 Kaliwungu, using the ADDIE reference model which is a commonly used model. The results of the research showed that the motion foot media was successful in increasing students' understanding of the material as the material validation presentation was 95.4%, media validation was 73.3%. Based on the questionnaire score given by the teacher, it was 100% and the student questionnaire was 94.9%.